The adventures of Captain Underpants : an epic novel - Pilkey, Dav, 1966- (Blue Sky Press, 1997)
When George and Harold hypnotize their principal into thinking that he is the superhero Captain Underpants, he leads them to the lair of the nefarious Dr. Diaper, where they must defeat his evil robot henchmen.